Persepsi Mahasiswa Jurusan Pendidikan Bahasa Arab Terhadap Tantangan dalam Memahami Pembelajaran Bahasa Arab di Universitas Muhammadiyah Bima - Siti Mutmainah; Sri Wahyuningsih; Nurdiniawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
At Muhammadiyah Bima University, Arabic language learning faces various challenges, ranging from students' diverse levels of understanding, the availability of learning resources, to the teaching methods applied by lecturers. In this context, the diversity of students' level of understanding can be caused by differences in educational background before entering college, previous experience in learning Arabic, and how often they are exposed to Arabic-speaking environments. So this research aims to find out the perceptions of students majoring in Arabic Language Education towards the challenges in understanding Arabic language learning at Muhammadiyah Bima University. This research will be conducted at the University of Muhammadiyah Bima which is located on Jln. Anggrek No. 16 Nae Village, West Rasanae Sub-District, Bima City, West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data collection techniques are observation, interview and documentation. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of the study, it can be concluded that students of the Arabic Language Education Department at Muhammadiyah Bima University have various perceptions of the challenges they face in understanding Arabic language learning. Most students realize that learning Arabic has its own level of difficulty, especially in grammatical aspects (qawaid), vocabulary mastery (mufradat), and listening and speaking skills (istima' and kalam). This perception shapes students' attitudes in responding to the learning process, both in terms of learning motivation and the strategies used.